Analysis of VEGF receptors and microvessel density in NMU-induced breast cancer under the influence of platelet factor 4 and rapamycin - Muhammad Sakri, Muhammad Shahidan (2015)
Breast cancer is the main killer disease among women worldwide and the second most common cause of cancer death in women in the United States. Angiogenesis is the formation of a new vascular network from the pre-existing vessels. It is a normal and vital process for growth and development as well as in wound healing and in the formation of granulation tissue. Neovasculation or angiogenesis play a pivotal role in the supply of essential nutrients and oxygen for cell growth and also providing passageway for tumour metastasis. Currently, angiogenesis is being intensively studied to inhibit tumour progression by blocking the process. In this study, the rats model were induced N-nitroso-N-methylurea (NMU) to cause invasive mammary tumourigenesis. The rats were divided into 4 groups based on treatment given; rapamycin, PF4 and drug combination. The rapamycin and PF4 were administered as single agent or in combination to determine the anti-tumour and anti-angiogenic effects as well as to evaluate their nature when combined. Flt-1, Flk-1, and Flt-4 were selected as markers for downstream mediators which represent the process of tumour angiogenesis, differentiation, cell proliferation and vascular permeability of NMU-model while CD34 marker had been selected for microvessel density (MVD) counting. The protein expressions and gene expression of these markers were evaluated using immunohistochemistry analysis and Real-time PCR assay. Findings from the control group had demonstrated that the severity of malignancy significantly increased with the progression of the mammary tumour. Development of less-aggressive lesion that was histologically classified as Invasive Ductal Carcinoma (IDC)-Cribriform subtype was predominant in small sizes of tumour. In contrast, development of more-aggressive lesions that were histologically classified as IDC-Papillary and Not Otherwise Specified (NOS) subtypes were seen in larger sizes of tumour. In the treatment group, rapamycin treatment had been found to show significant inhibition of mammary tumour progression as well as tumour angiogenesis at protein and gene level. All VEGF signaling receptor markers expressions were significantly suppressed which were associated to significant tumour regression. Treatment with PF4 alone is not effective to inhibit the tumour angiogenesis. This was reflected in the insignificant inhibition of Flt-1, Flk-1 and Flt- 4 expression. The drug combination had obtained a significant down-regulation of Flt-1, Flk-1 and Flt-4 at protein and gene level but no synergistic effects were seen. Microvessel density counting had revealed that there is correlation (p<0.01) between the existing of capillary and the expression of VEGF signaling molecule receptors. Less capillary formation was observed in less aggressive tumours while the converse was seen in aggressive tumours. Thus, the present findings had suggested that rapamycin was not synergistic or additive to PF4. In fact, PF4 might be antagonist towards the action of rapamycin as anti-tumour and anti-angiogenesis. Present findings had concluded that rapamycin is a potent anti-angiogenic agent for the invasive NMU-induced mammary carcinoma in the rat model and has the potential to be applied clinically as an anti-angiogenic therapy for the treatment of advanced stages of breast cancer.